Золотая гора - Кузнецов Юрий Поликарпович (Репро, 1993)
Перепеч.: М. : Молодая гвардия, 1990. Экземпляры: БС (20170803) / Инвентарный номер: РТШ48721 / Сис.шифр: Р2 / Авт.знак: К 89 / ГРНТИ: 17 / ББК: 84(2)